Variation in RBE for survival of V79-4 cells as a function of alpha-particle (helium ion) energy - Tracy, B; Stevens, D; Goodhead, D; Hill, M (Radiation Research Society, 2015)
High linear energy transfer (LET) α particles are important with respect to the carcinogenic risk associated with human exposure to ionizing radiation, most notably to radon and its progeny. Additionally, the potential use of alpha-particle-emitting radionuclides in radiotherapy is increasingly being explored. Within the body the emitted alpha particles slow down, traversing a number of cells with a range of energies and therefore with varying efficiencies at inducing biological response. The LET of the particle typically rises from between ~70–90 keV μm−1 at the start of the track (depending on initial energy) to a peak of ~237 keV μm−1 towards the end of the track, before falling again at the very end of its range. To investigate the variation in biological response with incident energy, a plutonium-238 alpha-particle irradiator was calibrated to enable studies with incident energies ranging from 4.0 MeV down to 1.1 MeV. The variation in clonogenic survival of V79-4 cells was determined as a function of incident energy, along with the relative variation in the initial yields of DNA double-strand breaks (DSB) measured using the FAR assay. The clonogenic survival data also extends previously published data obtained at the Medical Research Council (MRC), Harwell using the same cells irradiated with helium ions, with energies ranging from 34.9 MeV to 5.85 MeV. These studies were performed in conjunction with cell morphology measurements on live cells enabling the determination of absorbed dose and calculation of the average LET in the cell. The results show an increase in relative biological effectiveness (RBE) for cell inactivation with decreasing helium ion energy (increasing LET), reaching a maximum for incident energies of ~3.2 MeV and corresponding average LET of 131 keV μm−1, above which the RBE is observed to fall at lower energies (higher LETs). The effectiveness of single alpha-particle traversals (relevant to low-dose exposure) at inducing cell inactivation was observed to increase with decreasing energy to a peak of ~68% survival probability for incident energies of ~1.8 MeV (average LET of 190 keV μm−1) producing ~0.39 lethal lesions per track. However, the efficiency of a single traversal will also vary significantly with cell morphology and angle of incidence, as well as cell type.